Analytical and Simulation Studies of Gyroklystron Amplifiers - Chauhan, Madan Singh (Main Library, IIT (BHU), Varanasi, 2015)
Generation and amplification of RF waves in the millimeter wave and submillimeter wave frequency range is of importance to applications in high resolution radar and high information density communication, deep space and specialized satellite communication, advanced high gradient RF linear accelerators, plasma diagnostics and chemistry, material processing, waste remediation, ceramic sintering, laser pumping, power beaming and electron cyclotron resonance (ECR) heating of fusion plasmas, radar and imaging in atmospheric and planetary science, and nonlinear spectroscopy. However, there exists a technology gap for active devices in this frequency range. The conventional microwave tubes are not capable to generate high power at millimeter and submillimeter wave frequencies due to shrinking of their cross sectional dimension with frequency. For quantum-optical devices, like, lasers, it is difficult to sustain the population inversion with the reduction of the energy of each quantum in the lower frequency region. Therefore, during the past few decades, intensive research and development efforts have been made towards high power coherent gyro-sources and gyro-amplifiers in this frequency range. In gyro-devices, the problem of miniaturization of transverse dimensions with frequency has been tackled by using overmoded RF circuits, i.e., cavities and waveguides, thereby dramatic increase in their transverse dimension due to operation in the higher order modes.
Keywords: Amplifiers